Lâu rồi chưa ai xơi nên mình đành xơi vậy )
Đặt:
$A= 1+ \frac{2}{2^2}+\frac{3}{2^3}+\frac{4}{2^4}+...+ \frac{100}{2^{100}}$
$\Longrightarrow 2A= 2+1+\frac{3}{2^2}+\frac{4}{2^3}+...+ \frac{100}{2^{99}} $
$\Longrightarrow 2A-A=( 2+1+\frac{3}{2^2}+\frac{4}{2^3}+...+ \frac{100}{2^{99}})-(1+ \frac{2}{2^2}+\frac{3}{2^3}+\frac{4}{2^4}+...+ \frac{100}{2^{100}}) $
$\Longrightarrow A=2+1+\frac{3}{2^2}+\frac{4}{2^3}+...+ \frac{100}{2^{99}}-1- \frac{2}{2^2}-\frac{3}{2^3}-\frac{4}{2^4}-...- \frac{100}{2^{100}} $
$\Longrightarrow A=2+1+\frac{3}{2^2}+\frac{4}{2^3}+...+ \frac{100}{2^{99}}-1- \frac{1}{2}-\frac{3}{2^3}-\frac{4}{2^4}-...- \frac{100}{2^{100}} $
$\Longrightarrow A=1+ \frac{1}{2}+ \frac{1}{2^2}+\frac{1}{2^3}+...+ \frac{1}{2^{99}}- \frac{100}{2^{100}} $ (1)
Ta có:
$B= 1+ \frac{1}{2}+ \frac{1}{2^2}+\frac{1}{2^3}+...+ \frac{1}{2^{99}}$
$\Longrightarrow \frac{1}{2} B= \frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+ \frac{1}{2^{100}} $
$\Longrightarrow B- \frac{1}{2} B= 1+ \frac{1}{2}+ \frac{1}{2^2}+\frac{1}{2^3}+...+ \frac{1}{2^{99}}-\frac{1}{2}-\frac{1}{2^2}-\frac{1}{2^3}-...- \frac{1}{2^{100}} $
$\Longrightarrow \frac{1}{2} B= 1- \frac{1}{2^{100}} $
$\Longrightarrow B= 2- \frac{1}{2^{99}} $
Thay vào (1) ta có:
$A=2- \frac{1}{2^{99}} - \frac{100}{2^{100}}$
$A=2- \frac{51}{2^{99}}$
Last edited by a moderator: 12 Tháng năm 2012